ANALISIS KEUNTUNGAN USAHA PENGOLAHAN KOPI KOYA DI DESA KELURAHAN KOYA KECAMATAN TONDANO SELATAN KABUPATEN MINAHASA (ANALYZING THE BENEFITS OF KOYA COFFEE PROCESSING BUSINESS IN KOYA VILLAGE TONDANO SELATAN SUB-DISTRICT MINAHASA REGENCY) - Muhammad R. Hemeto; Vicky R.B Moniaga; Charles R. Ngangi (AGRI-SOSIOEKONOMI, 2021)
This study aims to analyze the benefits of koya coffee processing business in Koya village, Tondano Selatan sub-district, Minahasa regency. This research was conducted from March 2020 to June 2020. The data used in this study are primary data and secondary data. Primary data were obtained from direct interviews with 1 respondent, namely business owners using a questionnaire, while secondary data were obtained from agencies related to this study, among others, literature or previous research. The results showed that the cost in production per 6 months was Rp. 706,555 and income was Rp. 13,900,000 with a profit of Rp. 6,193,445.